2022
DOI: 10.1111/ppc.13107
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a psychiatric patient at home and work fatigue in family caregivers: The moderating effect of spirituality

Abstract: Objectives To assess the association between the mental health of caregivers having a psychiatric patient at home and work fatigue, and if this association is moderated by spirituality. Methods This case‐control study enrolled 600 caregivers (July–September 2019). Results Stress, anxiety, insomnia and the presence of a psychiatric patient at home were associated with higher levels of physical, mental, and emotional work fatigue. In the case of caregivers who have a psychiatric patient at home, those with low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…From a psychological perspective, it is associated with stress and other strong emotional experiences that may coexist with depression and anxiety disorders [57]. Caring for patients with severe psychiatric symptoms may lead to high levels of physical, mental and work fatigue among their caregivers [58]. A previous study conducted among insomnia patients found that the relationship between insomnia and fatigue was moderated by comorbid depression [55].…”
Section: Discussionmentioning
confidence: 99%
“…From a psychological perspective, it is associated with stress and other strong emotional experiences that may coexist with depression and anxiety disorders [57]. Caring for patients with severe psychiatric symptoms may lead to high levels of physical, mental and work fatigue among their caregivers [58]. A previous study conducted among insomnia patients found that the relationship between insomnia and fatigue was moderated by comorbid depression [55].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic (Sfeir et al, 2022). Park (2005) posits that spirituality adds meaning to incongruities of life, with Shelton et al (2020) elucidating that spirituality builds on individual resilience.…”
Section: Stressmentioning
confidence: 99%
“…Maltby et al (1999) and Waite et al (1999) have attributed the frequency of praying to boosting self-esteem and locus of control. Searching for a higher meaning in spiritual explorations within adversity can significantly reduce home and work fatigue (Sfeir et al , 2022). Park (2005) posits that spirituality adds meaning to incongruities of life, with Shelton et al (2020) elucidating that spirituality builds on individual resilience.…”
Section: Literature Reviewmentioning
confidence: 99%